Bhutan : Background Paper. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes economic development in Bhutan during 1990s. It highlights that since the 1980s, considerable importance has been placed on developing resource-based industries-spearheaded by large government hydropower, forestry, and mining projects-financed mainly with concessional foreign assistance. Consistent with the country's development philosophy, exploitation of forests has been carefully controlled owing to concerns about the impact on the environment. This paper also examines the financial and sectoral policies and related developments in Bhutan.